Negotiation and Communication Strategy of Pt. Concord Industry Indonesia in Improving Cooperation With Working Partners PT. Dwi Karya Prima (Outsourcing Company) Karawang Regency - July Yuliawati; M. Yani Syafei; Umi Narimawati (Dinasti Publisher, 2025)
This study aims to analyze the Negotiation Strategy and Communication carried out by PT. Concord with PT. Dwi Karya Prima (SDM) in improving Cooperation in the field of providing outsourcing workers. This study uses a qualitative descriptive method of conducting interviews and observations. The results of the study can be concluded for the Strategy carried out is Thorough Preparation by studying the company profile, business licenses, costs and advantages and disadvantages of the outsourcing party, finding solutions that benefit both parties, then two-way communication of mutual trust and honesty, mutually beneficial bargaining and avoiding conflict. For supporting factors, both parties must be clear about the goals of each in Cooperation, each must have a good reputation and track record in convincing partners, data and information must be complete regarding labor needs, costs and efficiency, conducting open dialogue and having a vision and mission that are in line. Communication Process Both parties carry out the communication process verbally and in writing, mutual trust between both parties, clear and complete price bargaining, communication in an interesting way and according to negotiation needs. The negotiation process was achieved and an agreement was agreed upon by both parties and signed by both parties. As for the inhibiting factors in the negotiation are Differences of views or opinions regarding the price or time of the negotiation, the data provided is less relevant and complete, frequent miscommunication due to lack of communication, lack of flexibility in communication and rigid, regulatory policies from the government are too complex.